Kinerja Perusahaan Sektor Pelayanan Jasa Bandar Udara - Rizka Ramayanti; Faizah Syihab (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
Economic Value Added (EVA) is formulated by Net income (Operating Profit after deducting tax), minus with the total cost of capital for the current year. This study aims to examine PT (Persero) Angkasa Pura II performances’ with EVA. The data is taken from 2015 to 2017. This study uses secondary data taken from the site of the company PT (Persero) Angkasa Pura II. The data is analyzed descriptively. The company's performance is calculated from Annual Report such as income statement, balance sheet and note to financial statement. Data Collection Procedure is the data of companies’ financial statements taken from the PT (Persero) Angkasa Pura II website as well as obtained from www.idx.co.id. The EVA result of this study indicates that the financial performance of PT (Persero) Angkasa Pura II in 2015 and 2017 is Rp. 246,088,298,072 and Rp. 295,797,566,500 or positive value. This means it can be interpreted that the company has a healthy performance in accomplishing the shareholders expectations and lenders. In contrary, the financial performance of PT (Persero) Angkasa Pura II in 2016 using EVA gives a value of Rp. - 75,766,762,046 or negative value which means that the company has an unhealthy performance in 2016 in achieving their expectations.